SUNDA AND CIREBON LANGUAGE INTERCULTURAL COMMUNICATION PROCESS IN EARLY CHILDREN'S ENVIRONMENT: STUDI DESKRIPTIF KUALITATIF DI KELOMPOK BELAJAR PENDIDIKAN ANAK USIA DINI AN NUR DESA BEBER KECAMATAN BEBER KABUPATEN CIREBON - Uun - Machsunah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2023)
ABSTRACT This study aims to determine how the intercultural communication process in the Early Childhood Education (PAUD) Learning Group (KB) environment, as well as knowing what are the factors that hinder it. The location of this research in Beber Village, Beber District, Cirebon Regency, is a place that borders Kuningan Regency with different cultural backgrounds. Descriptive qualitative. The aim is to describe the facts that have been found systematically, actually and factually, which views that only researchers are truly free and different outside the target research environment, and produce objective conclusions. This research focuses on how the communication process and what are the factors of communication barriers that exist in the PAUD environment. The results of the research in the intercultural communication process that occurs in the An Nur Early Childhood Education Learning Group (KB PAUD) environment are: Communication is usually done through the adaptation stage first. If communication is blocked or deadlocked due to language differences, they use Indonesian as a 'unifying' bridge so that communication can be more effective and the message conveyed as desired. Students of KB PAUD An Nur in their interactions with peers use a mixed language of Sundanese and Cirebon. Teachers who teach at KB PAUD An Nur when teaching in class use Indonesian as the language of instruction. But when interacting informally follow the language style of their students, Sundanese and Cirebon language. 4.Communication that occurs in the environment of KB PAUD An Nur, as well as in general in Beber Village, Beber Sub-district experienced a mixture (acculturation) of Javanese culture Cirebon and Sunda Kuningan so that the use of language is unique. 5.The mingling of language and culture in the educational environment makes one of the riches in the cultural repertoire in Indonesia, especially in the development of Islamic education-based communities. Keywords: Intercultural Communication Process, Language Differences, Communication Barriers, Indonesian Language